Carsharing experience fostering sustainable car purchasing? Investigating car size and powertrain choice - Hoerler, Raphael; van Dijk, Jeremy; Patt, Anthony; Del Duce, Andrea (My University, 2021)
Scholars suggest that carsharing may lead to a reduction in car ownership and car travel. Research on how carsharing is connected to other sustainable effects such as an increased openness to micro to mid-sized battery electric vehicles is limited, however. We thus adopted a stated choice survey with 995 participants from Switzerland to test the car purchase preference of mobility users with and without carsharing experience. Results suggest that - for people living in the countryside - carsharing users have a 3 times higher likelihood of choosing a micro to mid-sized battery electric vehicle compared to participants without carsharing experience. We find a similar trend for people living in the agglomerations. We therefore recommend policy makers and mobility planners to take these benefits into account when planning carsharing services and its role in mobility systems.
Keywords: Battery electric vehicle; Car size; Stated preferences; Sustainable mobility; Carsharing; Attitudes and values